Investigating hydrogel formation using in situ variable-temperature scanning probe microscopy - Barker, Emily; Goh, Ching Yong; Jones, Franca; Mocerino, Mauro; Skelton, B.; Becker, Thomas; Ogden, Mark (2015)
The assembly and disassembly of supramolecular gel fibres are observed in situ using variable temperature scanning probe microscopy. The results show that fibre formation can be monitored at high resolution at a surface, and the final fibre morphologies are broadly consistent with those found by ex situ analysis of the bulk gel. The impact of a gelation inhibitor upon the fibre morphology is successfully investigated, providing direct evidence for the mechanism of inhibition as a function of additive concentration.